Coping with emotions - Greene, Kimberly; Greene, Ran; Wilson, Nancy Rabuck; Educational Video Network (United States: Educational Video Network, 2002)
Anger, indiference, sadness, confusion and ecstatic happiness are emotions that manifest themselves frequently during the teen years. The hormones that change the body physically also have a great effect on a teenager's emotions. Discover the gamut of emotions that rule a teenager's life and what can be done to control them
Executive producer, George H. Russel
Narrator: C Markham Anderson & Ellen Gassie
Keywords: Emotional problems of teenagers; Emotions; Adolescence psychology; Anger in adolescence